The protective effect of anterior cruciate ligament reconstruction on articular cartilage: a systematic review of animal studies. Issue 2 (February 2019) - Deckers, C.; Stephan, P.; Wever, K.E.; Hooijmans, C.R.; Hannink, G.
Summary: Objective: It is unclear if anterior cruciate ligament (ACL) reconstruction can prevent the onset of degenerative changes in the knee. Previous studies were inconclusive on this subject. The aim of this study was to systematically review all studies on the effect of ACL reconstruction on articular cartilage in animals. Design: Pubmed and Embase were searched to identify all original articles concerning the effect of ACL reconstruction on articular cartilage compared with both its positive (ACL transection) and negative (sham and/or non-operated) control in animals. Subsequently a Risk of bias and meta analysis was conducted based on five outcomes (gross macroscopic assessment, medical imaging, histological histochemical grading, histomophometrics and biomechanical characterization) related to articular cartilage. Results: From the 19 included studies, 29 independent comparisons could be identified which underwent ACL reconstruction with an average timing of data collection of 23 weeks (range 1–104 weeks). Due to limited data availability meta-analysis could only be conducted for gross macroscopic damage. ACL reconstruction caused significant gross macroscopic damage compared with intact controls (SMD 2.0 [0.88; 3.13]). These findings were supported by individual studies reporting on histomorphometrics, histology and imaging. No significant gross macroscopic damage was found when ACL reconstruction was compared with ACL transection (SMD −0.64 [−1.85; 0.57]). Conclusion: This systematic review with an average follow up of included studies of 23 weeks (range 1–104 weeks) demonstrates that, in animals, ACL reconstruction does not protect articular cartilage from degenerative changes. The consistency of the direction of effect, provides some reassurance that the direction of effect in humans might be the same.